The fractal analysis - Powerful tool for geodynamic investigations - Boyko Ranguelov (Annals of Mathematics and Physics - Peertechz Publications, 2023)
This is a short review of fractal analysis applications in Bulgaria to investigate the geodynamics at the local, regional, and global levels.